2012
DOI: 10.1158/0008-5472.can-12-0509
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Suppresses NK Cell–Mediated Responses to Carcinogen-Induced Tumors and Metastases

Abstract: The NLRP3 inflammasome acts as a danger signal sensor that triggers and coordinates the inflammatory response upon infectious insults or tissue injury and damage. However, the role of the NLRP3 inflammasome in natural killer (NK) cell-mediated control of tumor immunity is poorly understood. Here, we show in a model of chemical-induced carcinogenesis and a series of experimental and spontaneous metastases models that mice lacking NLRP3 display significantly reduced tumor burden than control wild-type (WT) mice.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(133 citation statements)
references
References 51 publications
5
127
0
1
Order By: Relevance
“…Supporting our indication, AIM2 has been showed to participate in melanoma and squamous cell carcinoma metastasis (de Koning et al ., 2014). Similar to AIM2, another inflammasome, the NOD‐like receptor pyrin domain containing‐3 (NLRP3), inhibited lung cancer and colorectal cancer metastasis by suppressing natural killer cell‐mediated responses (Chow et al ., 2012; Dupaul‐Chicoine et al ., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Supporting our indication, AIM2 has been showed to participate in melanoma and squamous cell carcinoma metastasis (de Koning et al ., 2014). Similar to AIM2, another inflammasome, the NOD‐like receptor pyrin domain containing‐3 (NLRP3), inhibited lung cancer and colorectal cancer metastasis by suppressing natural killer cell‐mediated responses (Chow et al ., 2012; Dupaul‐Chicoine et al ., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The role of inflammasomes in MDSC recruitment and immunosuppression is further supported by a study reporting that tumors derived from Nlrp3 −/− mice exhibit less infiltrating MDSC than those from WT mice (van Deventer et al, 2010). Tumor-associated MDSC may suppress natural killer (NK) cells, which would explain why loss of NLRP3 increases the anti-metastatic function of NK cells in a B16-F10 lung metastasis model (Chow et al, 2012). IL-18 can also suppress the anti-metastatic effect of NK-cells and IL-18 depletion boosts immune surveillance function of NK cells in B16-F10 melanomas and CT26 colon cancers (Terme et al, 2011).…”
Section: Immune Regulation By Inflammasomes During Cancer Developmentmentioning
confidence: 91%
“…In one colorectal metastasis model, the inflammasome complex was found to suppress metastasis via NK cell activity (45), and others showed that NLRP3 signaling in hematopoietic compartment can be protective against tumorigenesis through bone marrow chimera studies (31,33). In other models, however, NLRP3 null mice had reduced lung metastasis with B16-F10 tumor cells (46). These examples highlight the complex association between the inflammasome complex and cancer, which were have been reviewed in detail (47)(48)(49).…”
Section: Caspase-1 Expression In the Tme Correlates With Worse Prognosismentioning
confidence: 99%